Changes in ionic conductance signature of nociceptive neurons underlying fabry disease phenotype - Namer, Barbara; Schmelz, Martin (Frontiers in neurology, 2017)
The first symptom arising in many Fabry patients is neuropathic pain due to changes in small myelinated and unmyelinated fibers in the periphery, which is subsequently followed by a loss of sensory perception. Here we studied changes in the peripheral nervous system of Fabry patients and a Fabry mouse model induced by deletion of α-galactosidase A (Gla-/0). The skin innervation of Gla-/0 mice resembles that of the human Fabry patients. In Fabry diseased humans and Gla-/0 mice we observed similar sensory abnormalities, which were also observed in nerve fiber recordings in both patients and mice. Electrophysiological recordings of cultured Gla-/0 nociceptors revealed that the conductance of voltage-gated Na+ and Ca2+ currents was decreased in Gla-/0 nociceptors, whereas the activation of voltage-gated K+ currents was at more depolarized potentials. Conclusively, we have observed that reduced sensory perception due to small fiber degeneration coincides with altered electrophysiological properties of sensory neurons.